Ion‐Migration Mechanism: An Overall Understanding of Anionic Redox Activity in Metal Oxide Cathodes of Li/Na‐Ion Batteries. Issue 47 (17th October 2022) - Lai, Yangyang; Xie, Huixian; Li, Peng; Li, Biao; Zhao, Along; Luo, Laibing; Jiang, Zewen; Fang, Yongjin; Chen, Shengli; Ai, Xinping; Xia, Dingguo; Cao, Yuliang
Abstract: The anionic redox reaction (ARR) has attracted extensive attention due to its potential to enhance the reversible capacity of cathode materials in Li/Na‐ion batteries (LIBs/SIBs). However, the understanding of its activation mechanism is still limited by the insufficient mastering of the underlying thermodynamics and kinetics. Herein, a series of Mg/Li/Zn‐substituted Na x MnO2 and Li x MnO2 cathode materials are designed to investigate their ARR behaviors. It is found that the ARR can be activated in only Li‐substituted Li x MnO2 and not for Mg‐ and Zn‐substituted ones, while all Mg/Li/Zn‐substituted Na x MnO2 cathode materials exhibit ARR activities. Combining theoretical calculations with experimental results, such a huge difference between Li and Na cathodes is closely related to the migration of substitution ions from the transition metal layer to the alkali metal layer in a kinetic aspect, which generates unique Li(Na)–O–□TM and/or □Li/ Na –O–□TM configurations and reducing reaction activation energy to trigger the ARR. Based on these findings, an ion‐migration mechanism is proposed to explain the different ARR behaviors between the Na x MnO2 and Li x MnO2, which can not only reveal the origin of ARR in the kinetic aspect, but also provide a new insight for the development of high‐capacity metal oxide cathode materials for LIBs/SIBs. Abstract : An ion‐migration mechanism is proposed to explain the different anionic redox reaction (ARR) behaviors between Mg/Li/Zn‐substituted Na x MnO2 and Li x MnO2 . The theoretical and experimental results indicate that ARR activation is closely related to the migration of substitution metal from the transition metal (TM) layer to the alkali metal layer in a kinetic aspect, and vacancies in the TM layers play a vital role to activate the ARR activities.